Implementasi Standar Nasional Pendidikan dalam Meningkatkan Mutu Pembelajaran di Sekolah - Yuliana Safitri; Siti Julaiha (Universitas KH. Abdul Chalim Pacet Mojokerto, 2026)
This article discusses the concept of SNP, its implementation in educational institutions, as well as the challenges and strategies to improve its achievement. The National Education Standards (SNP) serve as the primary quality framework that guides the implementation of education in Indonesia. This study employs a qualitative approach using a literature review method by analyzing official documents, books, and relevant scholarly articles. The findings indicate that although SNP plays a strategic role as a national quality benchmark, its implementation remains hindered by limited teacher competence, disparities in educational facilities, technological barriers, and suboptimal policy coordination. Strengthening teacher capacity, ensuring equitable distribution of educational facilities, utilizing educational technology, and implementing continuous evaluation systems are essential to optimize SNP implementation. With strong collaboration among stakeholders, the SNP can function as an effective and sustainable quality assurance instrument in the national education system. Effective implementation of the SNP has a direct impact on improving the quality of learning by promoting standardized instructional processes, enhancing student engagement, and supporting the achievement of learning outcomes. Furthermore, consistent adherence to SNP encourages the development of a conducive learning environment that fosters students’ cognitive, affective, and psychomotor competencies. With strong collaboration among stakeholders, the SNP can function as an effective and sustainable quality assurance instrument in the national education system.